Preparation of C–N co-doped zirconia electrospun nanofibers and their humidity sensing properties. Issue 19 (9th August 2022) - Zhang, Jingjing; Lv, Ze; Wang, Lianying; Guo, Ying
Abstract : C and N have been co-doped to improve the humidity sensing of zirconia, which shows fast response, short recovery and good repeatability. Abstract : Carbon and nitrogen co-doped ZrO2 (C–N/ZrO2 ) composites were systematically obtained via an electrospinning approach and a calcination process. The components of C and N were introduced by adding melamine to the electrospinning precursor solution. The effects of C and N doping amount on the morphology and the humidity sensing behavior of C–N/ZrO2 composites were studied. Compared with ZrO2, C–N/ZrO2 with a uniform nanofiber structure exhibits significant improvements in humidity sensing performance, such as fast response (2 s), short recovery time (15 s), negligible hysteresis (0.3195%) and excellent repeatability. The humidity sensing mechanism of the composites was explored. It turns out that the introduction of C and N components into ZrO2 facilitates charge separation and enhances electron mobility, which is an effective method to improve the sensing properties. Moreover, the nanofibers with a large specific surface area and a porous structure prepared by electrospinning provided more active sites available for the reaction with water molecules.